Pengaruh Electronic Customer Relationship Management terhadap Kualitas Pelayanan dan Customer Satisfaction - Cahyaningrum, Adinda; Hastuti, Indra; Suyatno, Agus (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The background of this research is that most consumers come to fulfill their needs. This is in accordance with Alfamart's mission of providing satisfaction to customers or consumers by focusing on superior quality products and services. CRM as an integration of processes, human capital and technology seeks the best understanding of the company's customer place and focuses especially on customer retention and relationship management. . This research uses field research, namely research in which the data is extracted through observations and data sources in the field, which means that researchers use data collection methods in qualitative research. With a qualitative approach because it is intended to understand the phenomenon of the research object and present the required data in a descriptive form. This technique is direct research in the field using interviews or observation. The influence of E-CRM on service quality greatly facilitates work in today's era because business strategies that integrate processes, people and technology can help attract sales prospects, convert them into regular customers, get comprehensive information about consumer behavior, retain existing customers and make consumers satisfied. the Alfamart Pakel 2 Karanganyar store to respond to problems related to the influence of E-CRM on the quality of this store's service is expected to always be consistent such as providing information to consumers